Introducing Agility into the Processes of Manufacturing Companies: A Method for Evaluating Success, Support and Applicability. (May 2022) - Heimicke, J.; Czech, C.; Schoeck, M.; Mueller, J.; Rapp, S.; Albers, A.
Abstract: Agile approaches are increasingly being used in appropriate use cases for the development of mechatronic systems.In the process of implementing agile elements in the development processes, the question of the success of the transformation often arises. In order to support the agile transition in measuring process improvement, a framework was developed that evaluates the success of the implementation process by means of interviews at 4 maturity levels in the transformation. The method was evaluated in 3 use cases. On this basis, continuous adaptations can be made to the implementation process.